THE ROLE OF PENCIL DRAWING IN DEVELOPING STUDENTS’ ARCHITECTURAL IMAGINATION - Yuldashev Solmonjon Iqboljon ugli (Journals Park Publishing, 2025)
This article provides a scientific analysis of the role of pencil drawing exercises in shaping architectural imagination among students in architectural education. The study explores how pencil drawing contributes to the development of key professional competencies such as spatial thinking, compositional balance, proportional perception, artistic reasoning, and aesthetic sensitivity. Empirical observations, diagnostic assessments, and statistical analyses confirm the direct impact of pencil drawing on the effectiveness of design-related coursework. The research also addresses the integration of pencil drawing with digital technologies and proposes practical recommendations for improving curriculum design and instructional methods in architectural programs.
Keywords: Pencil drawing, architectural imagination, spatial thinking, compositional reasoning, aesthetic perception, graphic competencies, architectural education.